2008
DOI: 10.1177/0269881108094300
|View full text |Cite
|
Sign up to set email alerts
|

Mystical-type experiences occasioned by psilocybin mediate the attribution of personal meaning and spiritual significance 14 months later

Abstract: Psilocybin has been used for centuries for religious purposes; however little is known scientifically about its long-term effects. We previously reported the effects of a double-blind study evaluating the psychological effects of a high psilocybin dose. This report presents the 14-month follow-up and examines the relationship of the follow-up results to data obtained at screening and on drug session days. Participants were 36 hallucinogen-naïve adults reporting regular participation in religious/spiritual acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
612
8
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 651 publications
(706 citation statements)
references
References 33 publications
48
612
8
15
Order By: Relevance
“…Psilocybin has been used for centuries in healing ceremonies (1) and more recently in psychotherapy (2); it is capable of stimulating profound existential experiences (3), which can leave a lasting psychological impression (4). However, despite a wealth of literature on its phenomenology, we currently know very little about how its effects are produced in the brain.…”
mentioning
confidence: 99%
“…Psilocybin has been used for centuries in healing ceremonies (1) and more recently in psychotherapy (2); it is capable of stimulating profound existential experiences (3), which can leave a lasting psychological impression (4). However, despite a wealth of literature on its phenomenology, we currently know very little about how its effects are produced in the brain.…”
mentioning
confidence: 99%
“…Similarly, a small open-label trial with psilocybin has found preliminary evidence of efficacy following a single dose in treatment-resistant depressed patients (43). In healthy humans, individuals have reported long-term increases in optimism following LSD (43) and increases in wellbeing and openness following psilocybin administration (44,45).…”
Section: Anti-depressant Effectsmentioning
confidence: 99%
“…Psychologically, it has been suggested that the psychedelic 'spiritual awakening', can give the individual a different perspective on life and a sense of meaning (62). Long-term changes in a person's outlook (44,45) could be critical in helping to maintain abstinence.…”
Section: Experiential Changesmentioning
confidence: 99%
“…Spiritual experiences are not rare, with five to forty percent of the general population reporting having had at least one spiritual or mystical experience (Allman et al, 1992;Davis & Smith, 1985;Greeley, 1974;Ring, 1985;Thomas & Cooper, 1978). Indeed, spiritual practices such as prayer, meditation, or entheogen use are associated with increased numbers of spiritual or mystical experiences (e.g., Lyvers & Meester, 2012;Walsh & Vaughan, 1991), and the occurrence of these experiences is correlated with wellbeing (e.g., Griffiths et al, 2011;Griffiths, Richards, Johnson, McCann, & Jesse, 2008;Griffiths, Richards, McCann, & Jesse, 2006;Hood, 1977;Maslow, 1994).…”
Section: Spiritualitymentioning
confidence: 99%